Transparansi Pengelolaan Keuangan Masjid Jami’ Al Jimahelah - Senoaji, Aditya Rizqi (Universitas Pahlawan Tuanku Tambusai, 2023)
Mosques receive funds from the community around the mosque, and prayer congregations in particular who are carrying out their worship at a mosque. Because it receives funds from the community, a concept for managing mosque financial funds is needed in the form of transparency in the use of mosque funds. The purpose of this article is to find out the form of transparency in managing the funds of the Jami' Al Jimahelah mosque so that the community as the largest contributor to funds for the mosque can feel safe and comfortable for the welfare of the people around the mosque. The data collection method for this research uses interviews. Interviews were conducted with mosque administrators who were tasked with managing mosque funds regarding all activities related to mosque funds, both in terms of income and expenditure. The results of the research can be concluded that transparency in the management of Al Jilahelah mosque funds is a mandatory thing that must be carried out by the mosque takmir. The form of transparency that has been implemented by the management of the Al, Jimahela mosque is by reporting verbally the management of mosque funds at every Friday prayer and reporting the management by sticking it on the information board available in the mosque.